Efficient Syntheses of Diverse N-Heterocycles: The Molybdenum(VI)-Catalyzed Reductive Cyclization of Nitroarenes using Pinacol as a Deoxygenating Agent - Gujjarappa, Raghuram; Vodnala, Nagaraju; Kabi, Arup K.; Kaldhi, Dhananjaya; Kumar, Mohan; Beifuss, Uwe; Malakar, Chandi C. (SynOpen, 2018)
Molybdenum(VI)-catalyzed domino reductive cyclization of nitroarenes has been devised for the syntheses of 1,4-benzoxazines and 1,4-benzothiazines in the presence of pinacol as deoxygenating agent. The scope of the described method was further extended to the syntheses of the rarely explored scaffolds, 1-hydroxyphenazines and quinoxalines. The present method avoids the use of hazardous deoxygenating agents and operates under solvent-free conditions.
Keywords: N-heterocycles; domino reaction; reductive cyclization; nitroarenes; dioxo-Mo(VI) complex; pinacol